Teleost TRAF7, a protein functions in the host antiviral responses via NF-κB and IRF3/7 mediated signaling - Li, Peng Tian; Li, Ying; Chen, Ying; Zhang, Jia Xi; Luo, Zi Hao; Zhang, Yi Fan; Jiang, Jing; Wang, Yi Lei; Zhang, Zi Ping; Jiang, Yong Hua; Zou, Peng Fei (Frontiers in Marine Science, 2023)
Tumor necrosis factor receptor-associated factors (TRAFs) play vital roles in tumor necrosis factor receptor (TNF-R) and interleukin-1 receptor/Toll-like receptor (IL-1R/TLR) mediated signaling pathway. However, the role that TRAF7 plays in the host immune response is largely unknown in comparison to the extensive and in-depth research that has been conducted on other members of the TRAF family. Notably, Lc-TRAF7, a cloned TRAF7 ortholog, was discovered in the large yellow croaker (Larimichthys crocea) in the current study, which has an open reading frame (ORF) of 1,962 base pairs and encodes a protein of 653 amino acids (aa). Lc-TRAF7 is consisted of a RING finger domain, a coiled-coil domain, and seven WD40 domains, with the genomic organization consisted of 20 exons and 19 introns. According to the expression analysis, Lc-TRAF7 was presented in a wide range of detected organs and tissues of the healthy fish, and was able to significantly induced by stimulations of poly I:C, LPS, PGN, and Pseudomonas plecoglossicida infection. Subcellular distribution analysis revealed that Lc-TRAF7 was a cytoplasmic protein, with the RING finger and coiled-coil domain function importantly in its subcellular localization. Luciferase assays demonstrated that Lc-TRAF7 overexpression significantly induced the activation of NF-κB, IRF3, IRF7, and IFN1 promoters. In addition, the WD40 domains play a pivotal role in the NF-κB promoter activation, whereas the RING finger and coiled-coil domain were essential in the IRF3, IRF7, and IFN1 promoter activation. Notably, Lc-TRAF7 overexpression could suppress SVCV proliferation in EPC cells, and the expression levels of IRF3, IRF7, ISG15, ISG56, RSAD2, and TNF-α were up-regulated under Lc-TRAF7 overexpression in LYCMS cells. These findings collectively implied that Lc-TRAF7 may function as an important regulator in the host antiviral responses via the NF-κB as well as IRF3/7 involved signaling pathways.